Stress Distribution in Luting Cement Layer in Implant Supported Fixed Partial Dentures Using Finite Element Analysis - Ehsan Ghasemi; Saber Khazaei; Farshad Bajgholi; Naeimeh Nasri; Pedram Iranmanesh (Islamic Dental Association of Iran, 2014)
Background and Aim : Luting cements are necessarily used to increase retention and enhance the marginal seal of fixed partial dentures (FPDs) . In this study, the finite element method (FEM) was used to investigate the effect of different types of luting agents on stress distribution in the luting cement layer i n a three-unit implant-supported FPD .   Materials and Methods : A three-dimensional (3D) FE model of a FPD was designed from the maxillary second premolar to the second molar teeth using CATIA V5R18 software, and analyzed by ABAQUS/CAE version 6.6 software . Three load conditions were statically applied to eight points in each functional cusp in horizontal (57.0 N), vertical (200.0 N) and oblique (400.0 N, θ=120°) directions. Five luting agents including glass ionomer, zinc polycarboxylate, polymer-modified zinc oxide eugenol (ZOE), composite resin and zinc phosphate were evaluated .   Results : The stress distribution pattern in the luting cement layer was almost uniform in all luting cements. In addition, the maximum von Mises stress in the luting cement layer (39.96 MPa) was at the cervical one-third of the palatal side of the second premolar when oblique force was exerted on zinc phosphate cement . Moreover, the minimum von Mises stress in the luting cement layer (0.41 MPa) was at the lateral side of the coronal one-third when the horizontal force was applied to the Polymer-modified ZOE cement. Likewise, the luting cement layers in the premolar tooth showed greater von Mises stress than that in molar tooth .   Conclusion : The type of luting cement has no significant effect on the stress distribution pattern in the luting cement layer however, von Mises stress values were different in various types of luting agents. USE of zinc phosphate cement is associated with more limitations .